An Approach to Design a Prototype of Lattice Structures: a Preliminary Study - Wojnicz, Wiktoria; Suraj, Keyru Salia; PIWKO, Klaudia; HIRSCH, Klaudia (Management and Production Engineering Review, 2026)
This paper investigates the mechanical response of lattice cells based on numerical models and 3D printed specimens. Considering the growing interest in the application of lattice structures in engineering and biomedical research, the design of lattice structures is becoming one of the key areas of modern materials engineering. The goal of this study is to develop author lattice cells that can be used in porous implants maintaining external compression loading. In the scope of this study, four author lattice cells were designed and produced from Acrylonitrile Butadiene Styrene (ABS) material using Zortrax M200 and Bambu Lab A1 3D printers (fused deposition modelling (FDM) technology) without using any supporting materials. A uniaxial compression test was performed using Zwick/Roell Z020. A numerical analysis of proposed lattice cells was conducted in FEBio and Abaqus. Young's moduli of all tested lattice cells were assessed from experimental and numerical data along with relative errors. The Young’s modulus was identified in the range: the smallest was 14.24 MPa (experimental) with 27.00/25.00 MPa (numerical) and the largest was 571.33 MPa (experimental) with 611.69/641.27 MPa (numerical). This study presents a validated numerical-experimental protocol that can be applied to produce FDM-printed lattice cell structures through closed iteration approach by considering given requirements along with technological limitations of FDM printings (manufacturing-induced flaws, staircase effects, and anisotropic polymer layer-bonding effects). Presented findings reveal that the designed topologies of lattice cells depend on the resolution of used 3D printers, however proposed numerical-experimental protocol offers a low-cost promising pathway for the early-stage design of patient-specific bone tissue implants.